(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
The aim of this paper is to present the results of an investigation conducted to identify the factors that determine the competitiveness of the regions of Mexico, as well as that stimulate or impede them. Specifically, it aims to identify the degree of competitiveness with the states of the country, according to indicators used globally, and also according to foreign direct investment, which is perhaps the variable that reflects the regional competitiveness. The paper has five sections. In Section I, provides introduction, Section II addresses the issue of economic competitiveness in the line that has been discussed recently at the international level. Section III addresses the issue of indicators to be used as a means to measure (or influence) regional competitiveness: competitiveness indicators of the World Economic Forum (WEF) and the Business Development Institute (IMD). Section IV includes a description of the methodology used and its measurement, consisting of two exercises: 1) The calculation by factor analysis, partial index (or influencing factors) of competitiveness, and, 2) Analysis Association to identify the elements that influence regional competitiveness, defined implicitly by the foreign direct investment. In Section V, conclusions are offered work and some final thoughts.